Urban Order or Legal Disorder? The Jerakah Flats Case in Semarang City Planning - Perdana, Dihyan Arga (Indonesian Journal of Agrarian Law, 2024)
Rapid population growth in Semarang City has prompted the government to develop vertical housing solutions in the form of flats as an alternative for low-income communities (MBR). This article analyzes the suitability of the Jerakah Flats development with the spatial planning principles stipulated in the Semarang City Spatial Plan (RTRW) and Regional Spatial Plan (RDTR), and evaluates the resulting social impacts on residents and the surrounding community. This article uses a normative juridical approach and sociological analysis to examine whether the Jerakah Flats development complies with zoning regulations and spatial efficiency principles, and the extent to which the project supports environmental sustainability. The resulting social impacts are complex, encompassing increased access to adequate housing, local economic opportunities, and challenges to social integration and equitable distribution of benefits. This study emphasizes the importance of inclusive and sustainable governance in vertical settlement planning in urban areas.